2023
DOI: 10.1097/aog.0000000000005171
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Relationship Between the Coronavirus Disease 2019 (COVID-19) Pandemic and Preterm Birth

Abstract: The onset of the coronavirus disease 2019 (COVID-19) pandemic was not associated with a change in the rate of preterm birth, regardless of socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…[9][10][11] One unexpected effect observed early during the pandemic was a population decrease in preterm birth rates, with reductions in preterm birth reported from many, [12][13][14][15][16][17] but not all, 18 countries. Studies from the United States also showed conflicting findings, [19][20][21][22][23][24][25][26][27][28] although the studies were not comparable because of heterogeneity with regard to populations (hospital, multicenter, population-based), study period, and study design or analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] One unexpected effect observed early during the pandemic was a population decrease in preterm birth rates, with reductions in preterm birth reported from many, [12][13][14][15][16][17] but not all, 18 countries. Studies from the United States also showed conflicting findings, [19][20][21][22][23][24][25][26][27][28] although the studies were not comparable because of heterogeneity with regard to populations (hospital, multicenter, population-based), study period, and study design or analysis.…”
Section: Discussionmentioning
confidence: 99%